Environmental conditions associated with carbonate-bearing rocks in lower Hawksbill Gap, Jezero western fan, Mars - Rebecca M.E. Williams; Joel A. Hurowitz; Linda C. Kah; Gwénaël Caravaca; Sanjeev Gupta; Nicolas Mangold; Michelle E. Minitti; R. Aileen Yingst; Kyle Uckert; Roger C. Wiens; Michael Tice; Megan Kennedy Wu; et al. (Icarus, 2026)

Digital health in acute care nutrition and dietetics practice: a scoping review - Oliver J. Canfell; Lily Van Horssen; Shangming Wang; Annemarie Knight; Courtney Hands; Selena Wu; Valeria Rucco; Alastair Duncan; Jaimon Kelly (Journal of the Academy of Nutrition and Dietetics, 2026)

The mid-temperature thermal framework of the East Antarctic margin from 50°E–150°E: Insights from apatite Lu-Hf and U-Pb geochronology - Ferdinand Mayer-Ullmann; Stijn Glorie; Jacob A. Mulder; Martin Hand; Laura J. Morrissey; Jacqueline A. Halpin (Gondwana Research, 2026)

CottonVaRx: A cotton variety recommender dashboard use case from Georgia, USA - Gonzalo J. Scarpin; Lavesta C. Hand; Phillip M. Roberts; Anish Bhattarai; Leonardo M. Bastos (European Journal of Agronomy, 2026)

A large cracticine passerine (Aves, Artamidae, Cracticinae) from the Early Miocene, St Bathans Fauna of New Zealand - Trevor H. Worthy; R. Paul Scofield; Suzanne J. Hand; Michael Archer; Vanesa L. De Pietri (PalZ, 2025)
A large fossil passerine (Aves, Artamidae, Cracticinae, Miostrepera canora gen. et sp. nov.), of Early Miocene (19–16 Ma) age, is described based on a proximal and a distal humerus from the lower Bannockburn Formation near St Bathans in Otago, New Zealand. Referred material includes a previously reported scapula and, tentatively so, a distal tibiotarsus. This taxon is the largest passerine in the St Bathans Fauna, in which the total passerine diversity may include up to 17 species. The only other named passerine in this fauna is a tiny acanthisittid wren, Kuiornis indicator . Cracticines (currawongs, magpies and butcherbirds) were absent in the native avifauna of New Zealand during the late Quaternary but are represented by the introduced Australian Magpie Gymnorhina tibicen now. The group is widespread in Australia with a fossil record extending to the Early Miocene. The presence of a Strepera -like cracticine in the Early Miocene in New Zealand indicates overwater dispersal to and colonisation of Zealandia from Australia that we suggest was facilitated by the diverse flora in the subtropical environments of Zealandia at the time. The subsequent loss of cracticines from the Zealandian avifauna is correlated with the marked loss in floral diversity following the climate cooling in the Middle Miocene and during the subsequent Pleistocene glacial oscillations. Furthermore, we show that the osteological correlates of the origin of musculus humerotriceps pars dorsalis are shown to be more complex than presence or absence of a dorsal fossa on the humerus.

Temporal and spatial distribution of chlorinated hydrocarbons in surface sediments of the Baltic Sea and Skagerrak over the past 30 years - Janika Reineccius; Mo Zhou; Ines Hand; Detlef E. Schulz-Bull; Joanna J. Waniek (Science of The Total Environment, 2025)

Within-herd mathematical modeling of Mycobacterium avium subspecies paratuberculosis to assess the effectiveness of alternative intervention methods - J. Reilly Comper; Karen J. Hand; Zvonimir Poljak; David Kelton; Amy L. Greer (Preventive Veterinary Medicine, 2025)

Early Miocene gull-like birds (Charadriiformes: Laridae) from New Zealand - Vanesa L. De Pietri; R. Paul Scofield; Suzanne J. Hand; Mike Archer; Alan J.D. Tennyson; Trevor H. Worthy (Geobios, 2025)

A synopsis of the Early Miocene St Bathans Fauna of New Zealand - Trevor H. Worthy; R. Paul Scofield; Vanesa L. De Pietri; Steven W. Salisbury; Werner Schwarzhans; Suzanne J. Hand; Michael Archer (Geobios, 2025)

Innovation in apatite Lu-Hf geochronology opens new opportunity for copper systems in southern Australia during the Nuna destruction - Jie Yu; Martin Hand; Justin L. Payne; Laura J. Morrissey; Alexander Simpson; Stijn Glorie; Yan-Jing Chen (Mineralium Deposita, 2025)
Precambrian iron oxide copper-gold (IOCG) systems have commonly experienced multiple mineralising and tectonothermal events and identifying their timing and geodynamic framework is challenging. World-class IOCG deposits in the Olympic Cu-Au Province, South Australia, are dominated by hematite and formed in the upper crust, while the magnetite-dominated Cu deposits hosted in granulite facies rocks are considered to represent the deeper expression of giant IOCG system. However, the application of novel in-situ Lu-Hf apatite geochronology reveals the magnetite-hosted Cu mineralisation is significantly younger and unrelated to the well-known ~ 1590 Ma Gawler Craton IOCG systems. Apatite Lu-Hf ages from the granulite that predates Cu mineralisation give ages of 1490 Ma. Infiltration of Cu-bearing fluids resulted in recrystallisation of apatite, LREE mobilisation and formation of secondary monazite. Lu-Hf ages for syn-mineralisation apatite give 1460 Ma, consistent with c. 1460 Ma U-Pb ages from secondary monazite. In contrast to the apatite in situ Lu-Hf ages, all apatite types produce a single U-Pb age of c. 1460 Ma, demonstrating the ability of Lu-Hf to preserve a more complete history of apatite formation than U-Pb in high- to medium-temperature rock systems. The timing of mineralisation coincides with the onset of Nuna fragmentation, representing a previously unrecognised driver for mineral system formation in southern Australia that installed Cu in crust previously dehydrated during a long history of granulite-grade tectonic events. The recognition of this Cu system in rocks generally considered unprospective shows that continental breakup can rejuvenate metallic systems in otherwise unprospective crust.

A new genus and two new species of malleodectid (Marsupialia, Malleodectidae) from the Middle and Late Miocene deposits of the Riversleigh World Heritage Area, northwestern Queensland. - Timothy J. Churchill; Michael Archer; Suzanne J. Hand (Journal of Mammalian Evolution, 2025)
Isolated upper teeth of a new fourth species of Malleodectes , M. arenai sp. nov. and an isolated lower molar representing a new genus of diminutive malleodectid, Weirdodectes napoleoni sp. nov. are described from Riversleigh’s Middle Miocene deposits. In addition, new malleodectid dental material from Middle and Late Miocene deposits at Riversleigh includes the first lower dentition of Malleodectes mirabilis and the first upper dentition of M. wentworthi . Comparisons of the upper and lower dentitions of M. mirabilis and M. wentworthi with that of the putative dasyurid Barinya wangala suggests that taxon is also a malleodectid. Parsimony and Bayesian phylogenetic analyses support a congeneric relationship between M. mirabilis and M. wentworthi , and support assignment of species of Barinya to Malleodectidae. These analyses support previous studies that found malleodectids were more closely related to dasyurids and myrmecobiids than to thylacinids. The snail-eating hypothesis for malleodectids is restricted to species of Malleodectes , with a more generalised durophagous diet suggested for B. wangala . The diet of Weirdodectes napoleoni sp. nov. is unknown but its dentition suggests it was highly specialised.

Neuromodulation by repetitive paired-pulse TMS at late I-wave intervals in older adults - Wei-Yeh Liao; Brodie J. Hand; Giuseppe Rinaldi; John G. Semmler; George M. Opie (Experimental Brain Research, 2025)
The efficacy of indirect (I) wave periodicity repetitive transcranial magnetic stimulation (iTMS) on the excitability of primary motor cortex (M1) in young adults can be modified by changing the late I-wave interval. Given that late I-wave activity is altered in older adults, this could contribute to age-related changes in M1 plasticity. To assess this possibility, the present study investigated the effects of iTMS using three late I-wave intervals (4.0, 4.5, and 5.0 ms) on M1 excitability in 17 older adults (69.6 ± 5.7 years; 10 females), which was compared to findings obtained previously in 17 young adults (27.2 ± 6.4 years, 12 females). Changes in M1 excitability were assessed using motor evoked potentials (MEPs) recorded from the right first dorsal interosseus to index single-pulse MEP 1.0mV and paired-pulse short-interval intracortical facilitation (SICF). To increase sensitivity to different intracortical circuits, both measures were also recorded using posterior-anterior (PA) and anterior-posterior (AP) TMS currents. Within older adults, PA MEP 1.0mV and SICF were facilitated following iTMS (both P < 0.0001) and these were not different between iTMS ISIs (both P > 0.077). In contrast, AP MEP 1.0mV and SICF were potentiated by iTMS 4.0 and iTMS 5.0 (both P < 0.023). iTMS 5.0 potentiation of AP circuits was also increased in older adults compared to young adults (both P < 0.004). These results suggest complex, timing-dependent effects of advancing age on the plasticity of the late I-wave circuits.

Comparison of naturally altered archaeological glasses from a marine environment with accelerated laboratory tests; implications for modelling long-term corrosion - Clare L. Thorpe; Nick Aldred; Stuart Creasey-Gray; Martin C. Stennett; Eperke A. Rencz; Susan Nehzati; Latham T. Haigh; Garry Manifold; Nishta Vallo; Christoph Lenting; Claire L. Corkhill; Russell J. Hand (Applied Geochemistry, 2025)

Cotton lint yield and quality variability in Georgia, USA: Understanding genotypic and environmental interactions - Gonzalo J. Scarpin; Anish Bhattarai; Lavesta C. Hand; John L. Snider; Phillip M. Roberts; Leonardo M. Bastos (Field Crops Research, 2025)

Temporal development of chlorinated hydrocarbons in the Baltic Sea sediments: Characterization of the pollution maximum - Mo Zhou; Ines Hand; Astrid Lerz; Matthias Moros; Detlef E. Schulz Bull; Joanna J. Waniek (Science of The Total Environment, 2025)

Dust in the Critical Zone: North American case studies - J. Brahney; R.C. Heindel; T.E. Gill; G. Carling; J.M. González-Olalla; J. Hand; D.V. Mallia; J.S. Munroe; K. Perry; A.L. Putman; S.M. Skiles; B.R. Adams; et al. (Earth-Science Reviews, 2024)

Investigating the Effects of Repetitive Paired-Pulse Transcranial Magnetic Stimulation on Visuomotor Training Using TMS-EEG - Ryoki Sasaki; Brodie J. Hand; Wei-Yeh Liao; John G. Semmler; George M. Opie (Brain Topography, 2024)
I-wave periodicity repetitive paired-pulse transcranial magnetic stimulation (iTMS) can modify acquisition of a novel motor skill, but the associated neurophysiological effects remain unclear. The current study therefore used combined TMS-electroencephalography (TMS-EEG) to investigate the neurophysiological effects of iTMS on subsequent visuomotor training (VT). Sixteen young adults (26.1 ± 5.1 years) participated in three sessions including real iTMS and VT (iTMS + VT), control iTMS and VT (iTMS Control + VT), or iTMS alone. Motor-evoked potentials (MEPs) and TMS-evoked potentials (TEPs) were measured before and after iTMS, and again after VT, to assess neuroplastic changes. Irrespective of the intervention, MEP amplitude was not changed after iTMS or VT. Motor skill was improved compared with baseline, but no differences were found between stimulus conditions. In contrast, the P30 peak was altered by VT when preceded by control iTMS ( P < 0.05), but this effect was not apparent when VT was preceded by iTMS or following iTMS alone (all P > 0.15). In contrast to expectations, iTMS was unable to modulate MEP amplitude or influence motor learning. Despite this, changes in P30 amplitude suggested that motor learning was associated with altered cortical reactivity. Furthermore, this effect was abolished by priming with iTMS, suggesting an influence of priming that failed to impact learning.

Analysis of Registered Dietitian Nutritionists (RDNs) Knowledge, Attitudes, and Beliefs on Transgender Nutrition Care in Michigan - J. Ford; E. Colling; D. Hannah; S. Hand (Journal of the Academy of Nutrition and Dietetics, 2024)

One billion years of tectonism at the Paleoproterozoic interface of North and South Australia - Laura J. Morrissey; Justin L. Payne; Martin Hand; Chris Clark; Matthew Janicki (Precambrian Research, 2023)

Radiogenic heat production drives Cambrian–Ordovician metamorphism of the Curnamona Province, south-central Australia: Insights from petrochronology and thermal modelling - Alexander T. De Vries Van Leeuwen; Tom Raimondo; Laura J. Morrissey; Martin Hand; Derrick Hasterok; Chris Clark; Robert Anczkiewicz (Lithos, 2023)

Descriptive network analysis and the influence of timescale on centrality and cohesion metrics from a system of between-herd dairy cow movements in Ontario, Canada - J. Reilly Comper; David Kelton; Karen J. Hand; Zvonimir Poljak; Amy L. Greer (Preventive Veterinary Medicine, 2023)

Untangling the ecological signal in the dental morphology in the bat superfamily Noctilionoidea - Camilo López-Aguirre; Suzanne J. Hand; Nancy B. Simmons; Mary T. Silcox (Journal of Mammalian Evolution, 2022)

Two new neoavian taxa with contrasting palaeobiogeographical implications from the early Miocene St Bathans Fauna, New Zealand - Trevor H. Worthy; R. Paul Scofield; Steven W. Salisbury; Suzanne J. Hand; Vanesa L. De Pietri; Michael Archer (Journal of Ornithology, 2022)
Two new neoavian landbirds are reported from the early Miocene St Bathans Fauna from New Zealand. Aegotheles zealandivetus sp. nov. is described from several bones, among which, notably, the tarsometatarsus shows more similarity to New Guinean taxa than to Australian—New Zealand species. Zealandornis relictus gen. et sp. nov. is described from a distal end of a humerus and placed in the new family Zealandornithidae, tentatively among the ‘higher landbirds’ Telluraves, with most similarity to coliiforms. The humerus is of similar size to that of species of Colius and its gracile shaft and very shallow sulcus scapulotricipitalis suggests reduced flying ability. The new species of Aegotheles reinforces the Australasian nature of the Zealandian fauna, while in contrast, Zealandornis relictus gen. et sp. nov. appears to have no close relatives. It is as distinct as Acanthisittidae and Strigopidae among birds, or Leiopelmatidae and Sphenodontidae among the herpetofauna, and like them, represents a similar relictual taxon. Together they confer a highly evolutionarily distinctive nature to the Zealandian fauna concomitant with a minimal 60 million years of isolation.

Utilising TMS-EEG to Assess the Response to Cerebellar-Brain Inhibition - R. Sasaki; B. J. Hand; W. Y. Liao; N. C. Rogasch; L. Fernandez; J. G. Semmler; G. M. Opie (The Cerebellum, 2022)
Cerebellar-brain inhibition (CBI) is a transcranial magnetic stimulation (TMS) paradigm indexing excitability of cerebellar projections to motor cortex (M1). Stimulation involved with CBI is often considered to be uncomfortable, and alternative ways to index connectivity between cerebellum and the cortex would be valuable. We therefore sought to assess the utility of electroencephalography in conjunction with TMS (combined TMS-EEG) to record the response to CBI. A total of 33 volunteers (25.7 ± 4.9 years, 20 females) participated across three experiments. These investigated EEG responses to CBI induced with a figure-of-eight (F8; experiment 1) or double cone (DC; experiment 2) conditioning coil over cerebellum, in addition to multisensory sham stimulation (experiment 3). Both F8 and DC coils suppressed early TMS-evoked EEG potentials (TEPs) produced by TMS to M1 ( P < 0.05). Furthermore, the TEP produced by CBI stimulation was related to the motor inhibitory response to CBI recorded in a hand muscle ( P < 0.05), but only when using the DC coil. Multisensory sham stimulation failed to modify the M1 TEP. Cerebellar conditioning produced changes in the M1 TEP that were not apparent following sham stimulation, and that were related to the motor inhibitory effects of CBI. Our findings therefore suggest that it is possible to index the response to CBI using TMS-EEG. In addition, while both F8 and DC coils appear to recruit cerebellar projections, the nature of these may be different.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Motor cortex plasticity and visuomotor skill learning in upper and lower limbs of endurance-trained cyclists - Brodie J. Hand; George M. Opie; Simranjit K. Sidhu; John G. Semmler (European Journal of Applied Physiology, 2022)

Age-related changes in motor cortex plasticity assessed with non-invasive brain stimulation: an update and new perspectives - John G. Semmler; Brodie J. Hand; Ryoki Sasaki; Ashley Merkin; George M. Opie (Experimental Brain Research, 2021)

3D Morphometric Analysis Reveals Similar Ecomorphs for Early Kangaroos (Macropodidae) and Fanged Kangaroos (Balbaridae) from the Riversleigh World Heritage Area, Australia - Kaylene Butler; Kenny J. Travouillon; Alistair R. Evans; Laura Murphy; Gilbert J. Price; Michael Archer; Suzanne J. Hand; Vera Weisbecker (Journal of Mammalian Evolution, 2021)

X-ray tomography of cryopreserved human prostate cancer cells: mitochondrial targeting by an organoiridium photosensitiser - Elizabeth M. Bolitho; Carlos Sanchez-Cano; Huaiyi Huang; Ian Hands-Portman; Matthew Spink; Paul D. Quinn; Maria Harkiolaki; Peter J. Sadler (JBIC Journal of Biological Inorganic Chemistry, 2020)
The organoiridium complex Ir[(C,N) 2 (O,O)] ( 1 ) where C, N = 1-phenylisoquinoline and O,O = 2,2,6,6-tetramethyl-3,5-heptanedionate is a promising photosensitiser for Photo-Dynamic Therapy (PDT). 1 is not toxic to cells in the dark. However, irradiation of the compound with one-photon blue or two-photon red light generates high levels of singlet oxygen ( 1 O 2 ) (in Zhang et al. Angew Chem Int Ed Engl 56 (47):14898-14902 10.1002/anie.201709082,2017 ), both within cell monolayers and in tumour models. Moreover, photo-excited 1 oxidises key proteins, causing metabolic alterations in cancer cells with potent antiproliferative activity. Here, the tomograms obtained by cryo-Soft X-ray Tomography (cryo-SXT) of human PC3 prostate cancer cells treated with 1 , irradiated with blue light, and cryopreserved to maintain them in their native state, reveal that irradiation causes extensive and specific alterations to mitochondria, but not other cellular components. Such new insights into the effect of 1 O 2 generation during PDT using iridium photosensitisers on cells contribute to a detailed understanding of their cellular mode of action. Graphic abstract

Assembly and characterisation of a unique onion diversity set identifies resistance to Fusarium basal rot and improved seedling vigour - Andrew Taylor; Graham R. Teakle; Peter G. Walley; William E. Finch-Savage; Alison C. Jackson; Julie E. Jones; Paul Hand; Brian Thomas; Michael J. Havey; David A. C. Pink; John P. Clarkson (Theoretical and Applied Genetics, 2019)
Key message A unique, global onion diversity set was assembled, genotyped and phenotyped for beneficial traits. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers. Abstract Conserving biodiversity is critical for safeguarding future crop production. Onion ( Allium cepa L.) is a globally important crop with a very large (16 Gb per 1C) genome which has not been sequenced. While onions are self-fertile, they suffer from severe inbreeding depression and as such are highly heterozygous as a result of out-crossing. Bulb formation is driven by daylength, and accessions are adapted to the local photoperiod. Onion seed is often directly sown in the field, and hence seedling establishment is a critical trait for production. Furthermore, onion yield losses regularly occur worldwide due to Fusarium basal rot caused by Fusarium oxysporum f. sp. cepae . A globally relevant onion diversity set, consisting of 10 half-sib families for each of 95 accessions, was assembled and genotyping carried out using 892 SNP markers. A moderate level of heterozygosity (30–35%) was observed, reflecting the outbreeding nature of the crop. Using inferred phylogenies, population structure and principal component analyses, most accessions grouped according to local daylength. A high level of intra-accession diversity was observed, but this was less than inter-accession diversity. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers, confirming the utility of the diversity set for discovering beneficial traits. The onion diversity set and associated trait data therefore provide a valuable resource for future germplasm selection and onion breeding.

The role of local sea surface temperature pattern changes in shaping climate change in the North Atlantic sector - Ralf Hand; Noel S. Keenlyside; Nour-Eddine Omrani; Jürgen Bader; Richard J. Greatbatch (Climate Dynamics, 2019)

Oxidative discolouration in whole-head and cut lettuce: biochemical and environmental influences on a complex phenotype and potential breeding strategies to improve shelf-life - Paul J. Hunter; Laura D. Atkinson; Laura Vickers; Stella Lignou; Maria Jose Oruna-Concha; David Pink; Paul Hand; Guy Barker; Carol Wagstaff; James M. Monaghan (Euphytica, 2017)
Lettuce discolouration is a key post-harvest trait. The major enzyme controlling oxidative discolouration has long been considered to be polyphenol oxidase (PPO) however, levels of PPO and subsequent development of discolouration symptoms have not always correlated. The predominance of a latent state of the enzyme in plant tissues combined with substrate activation and contemporaneous suicide inactivation mechanisms are considered as potential explanations for this phenomenon. Leaf tissue physical properties have been associated with subsequent discolouration and these may be influenced by variation in nutrient availability, especially excess nitrogen and head maturity at harvest. Mild calcium and irrigation stress has also been associated with a reduction in subsequent discolouration, although excess irrigation has been linked to increased discolouration potentially through leaf physical properties. These environmental factors, including high temperature and UV light intensities, often have impacts on levels of phenolic compounds linking the environmental responses to the biochemistry of the PPO pathway. Breeding strategies targeting the PAL and PPO pathway biochemistry and environmental response genes are discussed as a more cost-effective method of mitigating oxidative discolouration then either modified atmosphere packaging or post-harvest treatments, although current understanding of the biochemistry means that such programs are likely to be limited in nature and it is likely that they will need to be deployed alongside other methods for the foreseeable future.

Pomegranate dieback caused by Lasiodiplodia gilanensis in California - J. R. Úrbez-Torres; F. Peduto Hand; F. P. Trouillas; W. D. Gubler (European Journal of Plant Pathology, 2017)

A New Early Eocene (Ypresian) Bat from Pourcy, Paris Basin, France, with Comments on Patterns of Diversity in the Earliest Chiropterans - Suzanne J. Hand; Bernard Sigé; Michael Archer; Gregg F. Gunnell; Nancy B. Simmons (Journal of Mammalian Evolution, 2015)

Sexually Dimorphic Bandicoots (Marsupialia: Peramelemorphia) From the Oligo-Miocene of Australia, First Cranial Ontogeny for Fossil Bandicoots and New Species Descriptions - Kenny J. Travouillon; Michael Archer; Suzanne J. Hand; Jeanette Muirhead (Journal of Mammalian Evolution, 2015)

Age constraints on the timing of iron ore mineralisation in the southeastern Gawler Craton - K. Lane; E. A. Jagodzinski; R. Dutch; A. J. Reid; M. Hand (Australian Journal of Earth Sciences, 2015)

Projected changes in hailstorms during the 21st century over the UK - M. G. Sanderson; W. H. Hand; P. Groenemeijer; P. M. Boorman; J. D. C. Webb; L. J. McColl (International Journal of Climatology, 2015)
Hailstorms can pose a significant threat to society, by damaging property and disrupting livelihoods. An understanding of how hailstorm characteristics may change under a warming climate is therefore important for assessing the risk of hail damage for the insurance industry. A simple model of hailstone formation has been driven using meteorological data produced by a regional climate model (RCM) to project how hailstorm numbers and hailstone sizes could change during the 21st century in the UK . Evaluation of the modelled hailstone sizes, numbers and spatial distributions showed that they agreed reasonably well with observations. The effect of climate change on the numbers of damaging hailstorms in the UK (hailstones with diameters greater than 15 mm) was then investigated. A downward trend in the total number of damaging hailstorms during the 21st century was projected, with statistically significant trends for hailstones with diameters between 21 and 50 mm. Melting of hailstones made little contribution to the projected reductions. The results are subject to large uncertainties, some of which originate with the convective parameterization scheme used by the climate model.

Post-peak, fluid-mediated modification of granulite facies zircon and monazite in the Trivandrum Block, southern India - Richard J. M. Taylor; Chris Clark; Ian C. W. Fitzsimons; M. Santosh; M. Hand; Noreen Evans; Brad McDonald (Contributions to Mineralogy and Petrology, 2014)

Early Mesoproterozoic metamorphism in the Barossa Complex, South Australia: links with the eastern margin of Proterozoic Australia - L. J. Morrissey; M. Hand; B. P. Wade; M. Szpunar (Australian Journal of Earth Sciences, 2013)

Does insulin-like growth factor 1 genotype influence muscle power response to strength training in older men and women? - Suchi Sood; Erik D. Hanson; Matthew J. Delmonico; Matthew C. Kostek; Brian D. Hand; Stephen M. Roth; Ben F. Hurley (European Journal of Applied Physiology, 2012)

U–Pb zircon, zircon Hf and whole-rock Sm–Nd isotopic constraints on the evolution of Paleoproterozoic rocks in the northern Gawler Craton - K. E. Howard; M. Hand; K. M. Barovich; J. L. Payne; K. A. Cutts; E. A. Belousova (Australian Journal of Earth Sciences, 2011)

Genetic map construction and QTL mapping of resistance to blackleg (Leptosphaeria maculans) disease in Australian canola (Brassica napus L.) cultivars - S. Kaur; N. O. I. Cogan; G. Ye; R. C. Baillie; M. L. Hand; A. E. Ling; A. K. Mcgearey; J. Kaur; C. J. Hopkins; M. Todorovic; H. Mountford; D. Edwards; et al. (Theoretical and Applied Genetics, 2009)

African ancestry is associated with risk of asthma and high total serum IgE in a population from the Caribbean Coast of Colombia - Candelaria Vergara; Luis Caraballo; Dilia Mercado; Silvia Jimenez; Winston Rojas; Nicholas Rafaels; Tracey Hand; Monica Campbell; Yuhjung J. Tsai; Li Gao; Constanza Duque; Sergio Lopez; et al. (Human Genetics, 2009)

Temporal constraints on the timing of high-grade metamorphism in the northern Gawler Craton: implications for assembly of the Australian Proterozoic - J. L. Payne; M. Hand; K. M. Barovich; B. P. Wade (Australian Journal of Earth Sciences, 2008)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

The reference genetic linkage map for the multinational Brassica rapa genome sequencing project - Su Ryun Choi; Graham R. Teakle; Prikshit Plaha; Jeong Hee Kim; Charlotte J. Allender; Elena Beynon; Zhong Yun Piao; Pilar Soengas; Tae Ho Han; Graham J. King; Guy C. Barker; Paul Hand; et al. (Theoretical and Applied Genetics, 2007)

Identification of quantitative trait loci for resistance to Xanthomonas campestris pv. campestris in Brassica rapa - P. Soengas; P. Hand; J. G. Vicente; J. M. Pole; D. A. C. Pink (Theoretical and Applied Genetics, 2007)

Genetic analysis and mapping of resistance to lettuce dieback: a soilborne disease caused by tombusviruses - Rebecca C. Grube; William M. Wintermantel; Paul Hand; Rami Aburomia; David A. C. Pink; Edward J. Ryder (Theoretical and Applied Genetics, 2005)

Anoxia tolerance of con-familial tiger beetle larvae is associated with differences in energy flow and anaerobiosis - W. W. Hoback; J. E. Podrabsky; L. G. Higley; D. W. Stanley; S. C. Hand (Journal of Comparative Physiology B, 2000)

Multimodality multidimensional image analysis of cortical and subcortical plasticity in the rat brain - Alberto F. Goldszal; Oleh J. Tretiak; Demeral D. Liu; Peter J. Hand (Annals of Biomedical Engineering, 1996)

Characterization of a new polyomavirus (Polyomavirus papionis-2) isolated from baboon kidney cell cultures - Sylvia D. Gardner; Wendy A. Knowles; J. F. Hand; A. A. Porter (Archives of Virology, 1989)